A strategy to confront extremist ideas of terrorist organizations that lead to the spread of drugs - Ibrar Al-Nouri; Fayhaa Muhammad; Louay Salman (University of Mosul-college of Basic Education, 2024)
topic of drugs has occupied a significant space in literature and academic studies due to its profound and diverse impact on various social, political, economic, security, and religious aspects. The strategies to counter extremist ideas encompass political, economic, social, security, and religious dimensions and are adopted by various government entities. Through these strategies, efforts are made to strike and limit the spread of drugs, dismantle their foundations, and disrupt their plans to create an environment suitable for national security and the country's interests.    This study aims to elucidate the strategy to counter extremist ideas of terrorist organizations that lead to the dissemination of drugs. In other words, it seeks to contain and limit the spread of drugs prevalent throughout the country, understand their negative repercussions on all aspects of life, and identify the social and political characteristics of terrorist organizations.    The study also clarifies the main reasons and motivations that have led to a noticeable increase in drug prevalence. It gives political, security, and social dimensions a prominent place in studying this phenomenon and then diagnoses the effects of drugs on society.    The study reached several key results, the most prominent of which is the deployment of a strategy to confront extremist ideas leading to the spread of all types of drugs within the country. This is achieved by addressing the political, economic, and social dimensions of terrorist organizations sponsoring the production, marketing, and dissemination of drugs to achieve the study's objectives. The structure of the study consists of an introduction and three chapters.    The first chapter covers the conceptual introduction and the terms used, while the second chapter discusses the strategy to counter extremist ideas. The third chapter explores the dimensions of terrorist organizations in the spread of drugs, along with the results, recommendations, and a list of sources.